2016
DOI: 10.1080/03079457.2016.1156647
|View full text |Cite
|
Sign up to set email alerts
|

Timing of predisposing factors is important in necrotic enteritis models

Abstract: Since the ban of antimicrobial growth promotors, the importance of necrotic enteritis in broilers increases. Reliable and reproducible infection models are required for pathogenesis studies and product screening. Two major predisposing factors in necrotic enteritis models are fishmeal supplementation to feed and Eimeria infection. However, many unsolved issues regarding these predisposing factors still exist. Therefore, the influence of timepoint of fishmeal administration (onset on day 8 or day 18), timing of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…have been considered to be the important predisposing factors in reproducing the disease experimentally. Recently published studies showed that lesions of NE were observed when either Eimeria spp., fishmeal or the combination of both was administered as predisposing factors [ 25 , 30 , 35 ]. NE lesions induced by Eimeria spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…have been considered to be the important predisposing factors in reproducing the disease experimentally. Recently published studies showed that lesions of NE were observed when either Eimeria spp., fishmeal or the combination of both was administered as predisposing factors [ 25 , 30 , 35 ]. NE lesions induced by Eimeria spp.…”
Section: Discussionmentioning
confidence: 99%
“…At day 26 of age, the chickens were euthanized with inhaled carbon dioxide gas, and their digestive tracts were examined for gross necrotic lesions. The gross necrotic lesions in the small intestine (duodenum to ileum) were scored as described previously [ 10 , 35 ] as follows: 0=no gross lesion; 1=thin or friable walls with roughened mucosa; 2 =focal necrosis or ulceration (1–5 foci); 3=focal necrosis or ulceration (6–15 foci); 4=focal necrosis or ulceration (16 or more foci); 5=patches of necrosis 2–3 cm long; and 6=diffuse necrosis typical of field cases. Chickens with lesion scores of 2 or more were considered as NE positive.…”
Section: Methodsmentioning
confidence: 99%
“…NE produced by C. perfringens is a complex and multifactorial disease difficult to reproduce experimentally (Shojadoost et al 2012;Prescott et al 2016b;Van Waeyenberghe et al 2016). Several factors should be considered for a successful reproduction of experimental NE, including induction of intestinal damage with a coccidial infection, genetic background of the animals, size of feed particles, animal protein content and non-starch polysaccharides in the birds'diet, and C. perfringens strains used in the challenge, as well as the route, dose, and frequency of the infection (Stanley et al 2014;Rodgers et al 2015;Prescott et al 2016b;Van Waeyenberghe et al 2016;Oh and Lillehoj 2016).…”
Section: Experimental Models Of the Diseasementioning
confidence: 99%
“…There are many predisposing factors, such as viscosity of digesta, the presence of non-digestible polysaccharides, the gastrointestinal tract transit time and the intestinal pH, which are responsible for the ability of bacteria to cause the disease (Moore 2016;Yang et al 2019). One of the important factors is the coccidiosis caused by Eimeria species, which creates a suitable environment for the proliferation of CP (Si et al 2007;Van Waeyenberghe et al 2016). Due to coccidiosis, perforations are made in the intestinal epithelial lining, and plasma proteins accumulate in these holes.…”
Section: Introductionmentioning
confidence: 99%